Stillbirths: Incidence, Causes and Surrogate Markers of Intrapartum and Antepartum Fetal Deaths - Shanker, Ojasvi; Saini, Vandana; Gupta, Mamta (International Journal of Innovative Research in Medical Science, 2020)
Background: Stillbirth is a traumatic experience for both the patient and the obstetrician. Determining its cause and early interventions can reduce stillbirths. The study was undertaken to determine the incidence, evaluate causes and surrogate markers for intrapartum and antepartum stillbirths. Methods: A retrospective study was carried out from August 2015 to December 2018. All stillbirths more than 22 weeks or a birthweight of ≥500 g were included in the study. Demographic and all clinical details were collected from the indoor case records and cause of fetal death assigned. Results: There were 520 stillbirths and 28,580 deliveries in the study period. Majority of these women with stillbirths were in the age group of 20-25 years at 33-37 weeks period of gestation, had parity 1 to 3 and were unbooked. Intrapartum deaths accounted for only 8.46% stillbirths. Extreme prematurity was the most common cause for stillbirths (20.38%) followed by chorioamnionitis (16.73%), hypertensive diseases (15.77%) and abruption (10.38). The cause remained unknown in 53.27%. Fetal movement appeared a better surrogate of antepartum /intrapartum deaths than macerated/fresh stillborns. Conclusions: Incidence of stillbirths was 1.8%. Most of the deaths were antepartum (91.53%). Extreme prematurity was the commonest cause. Fetal movement appeared a better surrogate marker of intrapartum / antepartum deaths.